Facebook, news media and platform dependency: The institutional impacts of news distribution on social platforms. (August 2021) - Meese, James; Hurcombe, Edward
There is a growing concern around the dependency of news organisations on platforms like Facebook for audience traffic. However, scholars are still working out the extent of this dependency and how it manifests in practice. In this article, we draw on interviews with Australian news professionals and industry fieldwork to provide a nuanced account of this phenomenon. We find that news media organisations have recently started to diversify their distribution strategies and the business models associated with them in response to Facebook's algorithm changes. While Facebook remains important, we suggest that greater attention needs to be paid to the complex relationships that news organisations have with platforms. This article ends by considering the implications of these findings for international policy discussions centred around the prospect of platform regulation.